Equipment and Experimental Design for Reynolds Number Analysis - affan, muhammad; rizkiyanti putri, runita (Liaison Journal of Engineering, 2023)
Fluid flow properties is an important parameter in many industries, especially when designing an equipment. Fluid have three types of flow directions namely laminar, transitional or transient, and turbulent. Dimensionless number of Reynolds is the way to differentiate types of fluid flow based on a specific range of numbers. In this experiment, a simple yet effective equipment was design and built to produce laminar and turbulent flow. Moreover, the fluid flow also proven by the calculation of Reynolds number using known quantities from the experiment. Water at 25oC was chosen as the material for this experiment, but the other material can also be used in this equipment as long as it have low viscosity. The experiment was conducted five times and laminar flow produced from the equipment have Reynolds number of 1480, while turbulent flow showed much higher Reynolds number of 12760. Keywords: Fluid flow, Reynolds number, Laminar, Turbulent